2020
DOI: 10.1017/s002210901900098x
|View full text |Cite
|
Sign up to set email alerts
|

Board Gender Diversity and Corporate Innovation: International Evidence

Abstract: Using a novel database of firm patents and board characteristics across 45 countries, we examine both within- and cross-country determinants of board gender diversity and its relation to corporate innovation. Boards are more likely to include women in countries with narrower gender gaps, higher female labor market participation, and less masculine cultures. Firms with gender diverse boards have more patents and novel patents, and a higher innovative efficiency. Further analyses suggest that gender diverse boar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
122
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(128 citation statements)
references
References 69 publications
(63 reference statements)
5
122
1
Order By: Relevance
“…As the literature frequently states, empirical analysis in corporate governance studies can be complicated because many of the variables may be determined endogenously, which means that they are correlated with the error term. Endogeneity results in the potential existence of reverse causality, which implies that more women on boards can positively influence R&D, but at the same time, companies with higher R&D and a long-term orientation might be inclined to appoint more women as directors, due to their major focus on long-term performance [57]. In order to avoid the influence of this potential reverse causality, the literature suggests two procedures for analysing the effect of endogeneity, the use of instrumental exogenous variables and the inclusion of lag effects as instruments [53,58].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the literature frequently states, empirical analysis in corporate governance studies can be complicated because many of the variables may be determined endogenously, which means that they are correlated with the error term. Endogeneity results in the potential existence of reverse causality, which implies that more women on boards can positively influence R&D, but at the same time, companies with higher R&D and a long-term orientation might be inclined to appoint more women as directors, due to their major focus on long-term performance [57]. In order to avoid the influence of this potential reverse causality, the literature suggests two procedures for analysing the effect of endogeneity, the use of instrumental exogenous variables and the inclusion of lag effects as instruments [53,58].…”
Section: Resultsmentioning
confidence: 99%
“…This study also has policy-making implications and involves some suggestions for practitioners, related to the relevance of including women on boards to achieve greater innovation efforts in companies. The role of female directors has been widely analysed lately, in an effort to demonstrate their effect, mostly on firm performance [20,65], but also on corporate strategies, such as innovation [57], and to determine the critical mass needed to exert a real influence [12]. However, few studies have been devoted to identifying and demonstrating the characteristics and features that the female presence on the board should have to clarify and increase their influence.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the low female representation does not interfere with the positive effect of women's presence on environmental innovation initiatives [95]. Moreover, the presence of women on the board has certain benefits, such as greater innovation and creativity [60,146]. If these benefits outweigh the internal conflicts and other such negative effects arising from this greater board diversity [147], then environmental innovation may actually be enhanced.…”
Section: Variablesmentioning
confidence: 99%
“…Prior research on this subject has shown that boards with a higher percentage of women have higher stock liquidity through better monitoring and oversight abilities and more stock price informativeness of their respective companies (Ahmed and Ali, 2017;Gul et al, 2011). Another variable in boards' gender diversity is that there is a higher likelihood that women will be on a corporate board in countries with a narrow gender gap and less masculine cultures (Griffin et al, 2019). It must be stated that 90% of the most innovative companies analyzed in this paper are based in North America, compared to only 40% of the bioeconomy companies.…”
Section: Bioeconomymentioning
confidence: 99%